Place attachment and Involvement with rural wine tourism - Silva, Carla Maria (2021)
Tourism is motivated by the desire to experience distinct places and these places are typically perceived and linked to distinct images, emotions and meanings. The physical, natural and social and cultural elements of a place are important differentiating factors to attract, involve and attach people to them, both as visitors and residents. Place attachment and involvement has received increasing interest amongst tourism scholars, due to its obvious potential contribution to tourist loyalty and sustainable destination development. Still, despite the growing research on place-attachment and involvement in tourism, there is a lack of studies linking these constructs and specifically within wine regions. Within this context, the present conceptual work aims to present the concepts and dimensions of place-attachment and involvement in wine tourism based on an extensive literature review, from the scientific database Scopus, including the most relevant international scientific contributions in the field of tourism, with the keywords ‘place attachment’ and ‘involvement’ and ’wine tourism’.